Broadband rectangular microstrip antenna with slits for W-band applications - Mohammed Al-Shaibani, Badiea Abdulkarem; S.A. Gaid, Abdulguddoos; Abdullah,, Mohammed A.E.; Alomari, Mohammad Ahmed; Qaid, Mohammed M.S.; Alshammari, Majid Khalaf; Sallam, Amer (Engineering, Technology and Applied Science Research, 2025)
This work introduces a broadband rectangular patch antenna optimized for efficient data transmission in the W-band, particularly for 5G applications. By integrating two I-shaped slits with the radiating element, the antenna achieves an impressive performance, exhibiting wide bandwidth and excellent radiation characteristics. Utilizing Rogers RT5880 as the substrate material with a relative permittivity (εr) of 2.2, a small antenna with a size of 3.7 × 4.1 × 0.16 mm³ is realized. Extensive simulations are conducted using CST software in both frequency and time domains to optimize the antenna. The results show a notable 16% fractional bandwidth from 80.75 GHz to 94.79 GHz, with dual resonance frequencies at 84.5 GHz and 91.5 GHz, primarily a result of the incorporated slits. At 84.5 GHz, the antenna demonstrates an outstanding reflection coefficient of -66.37 dB, a Voltage Sanding Wave Ratio (VSWR) of 1.00096, a gain of 9.71 dBi, a directivity of 9.75 dB, and a high radiation efficiency of 91.8%. Similar trends are observed at 91.5 GHz, where the return loss remains at an impressive value of 55.92 dB and the VSWR maintains a very low value of 1.0032, indicating continued excellent impedance matching. While the gain (6.98 dBi) and directivity (7.05 dB) are slightly lower at this frequency, the radiation efficiency remains remarkably high at 94.9%, indicating efficient energy utilization. The wide bandwidth of the proposed design enables high data transfer rates, a crucial requirement for 5G networks. This translates to significant improvements in network capacity, allowing for more connected devices and data traffic. Additionally, the design exhibits excellent signal transmission characteristics, ensuring reliable data transfer. Finally, the antenna's compact size and efficient radiation have the potential to reduce power consumption in 5G devices, contributing to improved battery life and sustainability.